MANAJEMEN IMPRESI MICRO-INFLUENCER GENERASI Z DALAM MEMBENTUK PERSONAL BRANDING DI INSTAGRAM - Alifia Jilan Yusfina; Shadrina Rasyiqah Mulia (Bajang Institute, 2025)
As social media plays an increasingly significant role in digital marketing, micro-influencers now possess the power to influence public opinion and strategically shape their self-image. This research adopts a qualitative approach using a case study method, with in-depth interviews conducted with four active micro-influencers on Instagram. The findings reveal that the informants utilize nine key components of personal branding namely value, skill, behavior, total look, uniqueness, authenticity, achievement, strength, and goal to create an authentic and consistent self presentation. Self-promotion strategies are implemented through communication styles, visual content, and intensive audience interaction. The results indicate that personal branding functions not only as a tool for shaping one’s digital identity but also as a means to strengthen visibility and foster professional collaboration opportunities. This study is expected to contribute to the understanding of digital communication strategies, particularly in the context of individual branding on social media.